Distance Teaching in Law: Possibilities for Commonwealth Cooperation - John Goldring (Legal Education Review)
Most Commonwealth countries share the heritage of the common law. Many of them face difficulties in training a legal profession to meet current needs. In many areas Commonwealth countries are co-operating in education and training, but, to date, despite the efforts of the Commonwealth Legal Education Association, there has been little formal co-operation at the “academic” stage of legal education. Following the agreement of the Commonwealth Heads of Government at their 1987 Meeting, a new Commonwealth institution, The Commonwealth of Learning, was established in Vancouver, under the presidency of Dr James Maraj, formerly Vice-Chancellor of the University of the South Pacific. The Commonwealth of Learning will provide a clearing house and co-ordinating body for institutions carrying on distance teaching activities in different parts of the Commonwealth. Its establishment is seen as a means of developing existing expertise on distance teaching to solve problems which have arisen in Commonwealth countries over recent years.